VLA radio continuum and IRAS observations of the ring nebulae around WR 101 and WR 113 - Cappa, Cristina Elisabet (2002)
We report radio continuum observations at 1465 MHz obtained with the Very Large Array (VLA) in the DnC configuration toward the ring nebulae associated with the stars WR 101 and WR 113, with resolutions of ∼38″ and 30″, respectively. IRAS images of the nebulae with resolutions of about 2′ (90 M⊙, 40 cm-3) are also analyzed. A remarkable resemblance among the optical, infrared, and radio images of these ring nebulae is observed. The VLA data indicate that Anon. WR 101 is thermal in nature. An ionized mass of ≈230 ± 40 M⊙ and electron densities in the range ≈40-55 cm-3 were estimated for Anon. WR 101. The derived ionized masses and electron densities in the inner and outer shells of the nebula related to WR 113 are ≈20 ± 10 M⊙, 180-500 cm-3 and ≈90 M⊙ 40 cm-3, respectively. Based on infrared data at 60 and 100 μm, the derived masses and temperatures for the dust component in the ring nebula around WR 101 are 0.3-1 M⊙ and ≈40 K. The associated masses suggest that the ring nebula related to WR 101 and the outer arc associated with WR 113 consist of swept-up interstellar matter, while the relatively low ionized mass associated with the inner shell of the nebula around WR 113 may contain a nonnegligible contribution of expelled ejecta material. The derived electron densities for the nebula around WR 101 and the inner shell around WR 113 are comparable to electron densities for other W-R ring nebulae. Low filling factors are inferred for both nebulae. The nebulae probably originated during the current W-R phase of the stars.